Formulation and Antioxidant Activity of Lip Balm Containing Banana Peel (Musa paradisiaca var. Sapientum) Methanol Extract - Jastria Pusmarani Pusmarani (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Banana peel (Musa paradisiaca var. Sapientum) contains flavonoid, phenolic and tannin compounds as high source of antioxidant that can inhibit free radical reaction. Antioxidant were exhibited to hydrate, soften, and reduce dryness of the skin, and it can be potentially used as a lip balm formulation. This study investigated the stability of lip balm formulation contains banana peel methanol extract include pH test, homogeneity test, hedonic test, and evaluated antioxidant activity with DPPH method. This study used experiment laboratory method with banana peel methanol extract concentrations of 5%, 7.5%, and 10%, respectively. According to the results of this study, banana peel was made in form lip balm formulation, and it has homogeneous with suitable pH (5-6), no irritation and stable in storage at temperatures room (250). The hedonic test showed that lip balm contains banana peel with concentration of 7.5% and 10% were the most preferred by panelist. The antioxidant activity was exhibited an inhibition concentration of 50% (IC50). Lip balm of banana peel methanol extract of 5%, 7.5% and 10% were showed antioxidant activity with IC50 value of 44.910 ppm, 10.887 ppm and 61.930 ppm, respectively. Antioxidant activity of lip balm contains banana peel formulation with concentration of 5% and 7.5% were classified as very strong antioxidants. Lip balm containing banana peel formulation concentrations of 10% was categorized as a strong antioxidant. In this study, all lip balm formulation can be declared stable. In addition, lip balm contains banana peel methanol extract exhibited antioxidant properties and it can be made into a natural cosmetic formulation such as a lip balm.